2020
DOI: 10.5888/pcd17.190440
|View full text |Cite
|
Sign up to set email alerts
|

State and Regional Variation in Prescription- and Payment-Related Promoters of Adherence to Blood Pressure Medication

Abstract: What is already known on this topic? Approximately three-fourths of US adults with hypertension do not have their blood pressure controlled. Medication adherence is important in hypertension management and can be affected by how medications are prescribed and purchased. What is added by this report? We found considerable variation in prescription-and payment-related factors that promote medication adherence by geography and across the largest patient market segments comprised of medication prescriber, insuranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This allows us to track patients longitudinally even if they switch insurers or pharmacies. This dataset is regularly used in medical, regulatory, and policy research, as well as by commercial firms like pharmaceutical and insurance companies [e.g., 6 – 9 ]. The extract from this dataset that we received contains de-identified data on 9.4 billion prescription claims from more than 252 million patients between May, 2019 and August, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This allows us to track patients longitudinally even if they switch insurers or pharmacies. This dataset is regularly used in medical, regulatory, and policy research, as well as by commercial firms like pharmaceutical and insurance companies [e.g., 6 – 9 ]. The extract from this dataset that we received contains de-identified data on 9.4 billion prescription claims from more than 252 million patients between May, 2019 and August, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…32,33 Besides insurance, the regional variation in adherence can also be affected by factors like polypharmacy and complex drug regimens involving taking multiple pills at different times of the day, poor access to pharmacies especially in rural areas, and higher out-ofpocket expenses in areas with predominantly low-income populations. 34 These can be rectified by introducing better prescription practice guidelines involving generic fixed-dose drug combinations which will reduce the costs as well as the number of pills, increasing doorstep delivery of medications by switching to mail-order or online pharmacy practices. 35,36 Our results also revealed that CRMN was higher among current smokers compared to non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed‐dose combinations are evidence‐based but underutilized, comprising only 12% of all national BP medication fills in 2017, with considerably lower values in southern states where hypertension‐related CVD death rates are high. 54 Increasing adherence to these medication regimens is critical. Despite the 706.5 million BP medication prescriptions filled in the United States in 2017, only half of treated patients followed physicians’ instructions, with lower adherence among Black adults and in the South.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the 706.5 million BP medication prescriptions filled in the United States in 2017, only half of treated patients followed physicians’ instructions, with lower adherence among Black adults and in the South. 54 , 55 , 56 Finally, improved telehealth capabilities could optimize clinical care, especially in counties with limited access to care. Telehealth visits have increased during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%